The self-referentiality of two kinds of people --Character Types and Their Psychological Analysis in Pai Hsien-yung’s Taipei People - Na, Sai (Transactions on Social Science, Education and Humanities Research, 2024)
Two distinct types of people are featured in Pai Hsien-yung's novel "Taipei People": the ‘Root Breakers,’ who have severed their ties to the past, and the ‘Root Seekers,’ who are deeply rooted in their memories. This essay delves deeply into the inner lives of the characters from the author's perspective while also providing a detailed analysis of these two categories of characters and examining the interactions and collisions between various characters in Taipei People.